Assessment of noise pollution in operating theatre - Svardagalou, Paraskevi; Kalogianni, Antonia; Papageorgiou, Dimitris (Health & Research Journal, 2018)
Introduction: Noise is considered as a common and widespread problem in the working environment. There is a matter of noise pollution in operating theatres, which has side effects on health and working efficiency of the personnel. Aim: The assessment of the level of noise in the operating room and the analysis of the burnout and health effects of the healthcare staff working in a tertiary hospital. Material and Methods: Measurements were performed with sound meters in all three operating theatre zones during all three shifts. At the same time, the effect of noise on workers was investigated through self-completion of questionnaires during their work. Results: The results of the medical staff have shown that the workplace is noisy (59.2%) and 53.4% stated that the noise is disturbing. The majority of physicians (70%), in terms of their health effects due to noise, said they were not significantly affected, with the exception of anxiety and discomfort (40%). Relatively high professional burnout has proven in medical staff (75,7% high depersonalization and 48,6% emotional exhaustion) . As far as the responses of the nursing staff are concerned, 63% said that the workplace was noisy and 53.7% replied that the noise was disturbing. The nursing staff also stated that they are irritable (37,1%) and they feel stress(48,2%) and fatigue(72,2%). The professional burnout of nurses was also high (59,3% high depersonalization and 61,1% emotional exhaustion) . Statistically significant differences were found between medical and nursing staff in assessing exposure to noise and the symptoms caused by it, with nursing staff being more influenced by operating room noise (p≤0.05). Differences were also found among workers in different operational zones and specialties (p≤0.05). Conclusions: The results suggest the presence of noise pollution with impact on working performance. Noise effected health staff in a negative way due to specialty, different operational zone and burn out levels.